Tess of the d’Urbervilles: Hardy’s Journey towards Postmodernism - Hunar Shah,; Dr. Samina Ashfaq,; Kaleem Ullah Abid,; Huma Khan,; Maryam Munir,; Shah Zamin,; Fateh Khan, (Al-Qanṭara, 2024)
This research work attempts to explore the novel Tess of the d’Urbervilles from postmodern perspective. Tess of the d’Urbervilles transforms the concept of Victorian society, marking a transition from Victorianism to Postmodernism. The study reveals that Hardy portrays Tess more a postmodern than a Victorian character that she challenges Victorian chastity and virginity as meta- narratives in Tess of the d’Urbervilles. She defies the notion of female chastity by bearing an illegitimate child and rejecting the social stigma attached to it. She challenges traditional expectations regarding women's purity, class boundaries, and the consequences of social judgment. She refuses to conform to a forced marriage, asserting her agency and autonomy in the face of social constraints. In the novel, she resists patriarchal control and dominance, including her father, Alec d'Urberville, and Angel Clare. Tess's tragic fate is shaped by social expectations of purity and virtue, which she ultimately rebels against. Tess of the d’Urbervilles transforms the concept of Victorian society, marking a transition from Victorianism to Postmodernism. This research analyses themes of Tess’s rebellion against social norms: religion, morality, sexuality, and purity. Tess's character challenges such conventions, facing harsh consequences for daring to defy them. Postmodern theory is applied to the text, as such the proposed study is qualitative. This study intends to explore the postmodernist viewpoints of Jean Francois Lyotard, Jacques Derrida, Michel Foucault, Jean Baudrillard and Richard Rorty. Selected passages from the text are interpreted keeping in view postmodern theorists. Research approach is inductive. Research technique is interpretive content analysis. Tess of the d'Urbervilles can be analysed through a psychoanalytic lens, particularly in its exploration of the unconscious mind, repressed desires, and the impact of social expectations on individual behaviour.